The Implementation of Economic and Social Council's Duties as a United Nations Organs - Rais, Natasya Fila (Veteran Law Review, 2019)
This article will describe the history of the Economic and Social Council based on the documents underlying the establishment of the Economic and Social Council. In addition, the duties and authority of the Economic and Social Council as a committee of the United Nations will also be explained in this article, as well as the roles of the Economic and Social Council in cooperation with the agencies of the United Nations, which not only affect the continuity of the United Nations, but also affect the lives of the subjects of international law. The paper also comes with an analysis of the duties and authority of the Economic and Social Council as a committee of the United Nations. Other than that, analysis regarding the implementation of the role of the Economic and Social Council in cooperation with the agencies of the United Nations others joined outlined in this paper. It is expected that the contents of this paper can be useful not only as a reference for the learning process, but also as a form of contribution to the related sciences Law International and Regional Organizations.